The Absurd as a Representation: Towards a Hermeneutics of the Inexplicable (The Problematic Case of Godot) - Rybińska, Krystyna (Studia Anglica Posnaniensia, 2017)
This article attempts to re-signify the already extensively discussed conception of the absurd attributed to the aesthetic phenomenon presented by the so-called theatre of the absurd by critically reconsidering its paradigmatic work Waiting for Godot in relation to philosophical hermeneutics (Heidegger, Gadamer, Ricoeur). The fact that Beckett’s artistic method invalidates the transparency of the mirror-like relation between reality and art is known, and yet the potential theoretical consequences of such a literary revolution do not seem to have been exhausted - particularly in respect to the category of the absurd. Hence, the presented inquiry aims to view the phenomenon quite against its common conceptualizations derived from existentialist philosophy in order to indicate a possible route of exploring it from a hermeneutic perspective and thereby challenging, to some extent, Simon Critchley’s (2004: 165) famous assertion that Beckett’s oeuvre seems “uniquely resistant to philosophical interpretation”.